EFFECTS OF FIBER ORIENTATION AND HUMIDITY ON FRICTION AND WEAR PROPERTIES OF GRAPHITE FIBER COMPOSITES - SHIM, HH; KWON, OK; YOUN, JR (ELSEVIER SCIENCE SA LAUSANNE, 1992)
Friction and wear behavior of a unidirectional high modulus carbon fiber reinforced epoxy composite exposed to high and low humidity was experimentally examined under various sliding conditions. Experimental results showed that moisture adsorbed at the sliding surfaces greatly influences friction and wear properties of the composite. It was also discovered that the differences in friction and wear behavior of specimens with different fiber orientations are mainly due to the anisotropic properties caused by the microstructure of oriented graphite crystals in the carbon fibers and the macrostructure of fiber orientation in the matrix.